Life between the weakness of the terrestrial body and the hope of the celestial body: An analysis of 2 corinthians 5.1-10 - Wiese, Werner (Vox Scripturae - Revista Teológica Internacional, 2015)
Paul ‘s life was marked by suffering and hope. He felt the fragility of life so far as to compare it to a brittle clay pot. At the same time carried Paul himself an unyielding hope. It was not a hope for glorious and triumphant days in this life, to show public success as a follower and apostle of Jesus Christ, but his hope was centered on God, who will give him and us a new body at Christ’s coming. While it does not happen, Paul sees in his and in our fragile earthly body the time and place for God to act. Therefore sought to please God and serve him until the end of the story.